Bulk-scale synthesis of randomly stacked graphene with high crystallinity. (15th November 2021) - Xu, Zizhao; Nakamura, Shingo; Inoue, Taiki; Nishina, Yuta; Kobayashi, Yoshihiro
Abstract: Since the strong interlayer interaction of AB-stacked graphene in bulk form degrades the superior property of single-layer graphene, formation of randomly stacked graphene is required to apply the high performances of graphene to macroscopic devices. However, conventional methods to obtain bulk-scale graphene suffer from a low crystallinity and/or the formation of a thermodynamically stable AB-stacked structure. This study develops a novel approach to produce bulk-scale graphene with a high crystallinity and high fractions of random stacking by utilizing the porous morphology of a graphene oxide sponge and an ultrahigh temperature treatment of 1500–1800 °C with ethanol vapor. Raman spectroscopy indicates that the obtained bulk-scale graphene sponge possesses a high crystallinity and a high fraction of random stacking of 80%. The large difference in the random-stacking ratio between the sponge and the aggregate samples confirms the importance of accessibility of ethanol-derived species into the internal area. By investigating the effect of treatment temperature, a higher random-stacking ratio is obtained at 1500 °C. Moreover, the AB-stacking fraction was reduced to less than 10% by introducing cellulose nanofiber as a spacer to prevent direct stacking of graphene. The proposed method is effective for large-scale production of high-performance bulk-scale graphene. Graphical abstract: Image 1